TEKNIK KOMUNIKASI TERAPEUTIK DOKTER SEBAGAI UPAYA MEMOTIVASI PASIEN KANKER PAYUDARA DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Usmalya Juana Rifsa; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study examines the practice of therapeutic communication as one ofthe scientific study, especially health communication, in which communication isrequired in the treatment process, both humanistic and interpersonal skills, in thiscase involved the doctors and woman with breast cancer. This study designed todetermine the therapeutic communication techniques by the doctors to patientswith breast cancer in RSUD Arifin Achmad Hospital province of Riau andanalyzes the driving and inhibiting factors that relate to the success of it.The research was conducted at RSUD Arifin Achmad Hospital province ofRiau, located in Diponegoro street. This study took place from September 2013 toJanuary 2014. The method used in this study is qualitative study. Researchsubjects consisted of two oncology specialists who deal with breast cancerpatients at RSUD Arifin Achmad Hospital and six patients as additionalinformants. Datas were collected through observation and interviews.Results of this study indicate that therapeutic communication techniquesperformed by oncology surgeons at RSUD Arifin Achmad Hospital consisted oflistening, asking, sharing perceptions, clarifying, informing, changingperspectives, and assisting fears of the patients in humorous way. The supportingfactors for succesfull therapeutic communication techniques to the breast cancerpatients at RSUD Arifin Achmad Hospital are the openness of patients to thedisease, the patient's confidence to the treatment performed by doctors, familysupport, and treatment facilities owned by RSUD Arifin Achmad Hospital. Whileinhibiting factor are the patients less focus in listening explanation from doctors,patients too much asking questions, patient education background, doctors tightschedule, and clinic conditions that always crowded.Keywords: Therapeutic Communication, Interpersonal Communication, BreastCancer